External trade policy and the Sustainable Development Goals: Implementing the SDGs will meet justified criticisms of globalisation - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2017)
In 2015 the international community adopted the 2030 Agenda for Sustainable Development to "end all forms of poverty, fight inequalities and tackle climate change, while ensuring that no one is left behind". Trade can contribute to meeting those goals, but only if the policies are adapted accordingly. Given that they largely build on existing international commitments, the Sustainable Development Goals (SDGs) are not demanding revolutionary change. But it is an important step forward that the Agenda lays out a comprehensive programme for all policy areas, indicating what would be required to achieve sustainability at all levels. Especially in developed countries, there is widespread criticism that trade policy and globalisation worsen inequalities within and between states, endanger ecological stability and social security, and perpetuate unsustainable patterns of consumption. Implementing the SDGs would also represent a constructive response to these justified criticisms of globalisation.
Keywords: 320